On the complex moment problem on radial rays - Zagorodnyuk, S. M. (Журнал математичної фізики, аналізу, геометрії, 2005)
The complex moment problem in the case when the support of the measure lies on the algebraic curves P_N={zC: z^N -z^N=0}, N=1,2,3,…, is studied. For N=2,3 the necessary and sufficient conditions of solvability are obtained and all solutions of the problem are described. It is shown how this problem for arbitrary N is connected with the Hamburger moment problem with parameters. Mathematics Subject Classification: 44A60.